2005
DOI: 10.1590/s0100-879x2005000800013
|View full text |Cite
|
Sign up to set email alerts
|

High pressure-sensitive gene expression in Lactobacillus sanfranciscensis

Abstract: Lactobacillus sanfranciscensis is a Gram-positive lactic acid bacterium used in food biotechnology. It is necessary to investigate many aspects of a model organism to elucidate mechanisms of stress response, to facilitate preparation, application and performance in food fermentation, to understand mechanisms of inactivation, and to identify novel tools for high pressure biotechnology. To investigate the mechanisms of the complex bacterial response to high pressure we have analyzed changes in the proteome and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…More precisely, GrpE is a co‐chaperone working as a nucleotide exchange factor for DnaK (a heat shock protein belonging to the Hsp70 family) and it activates the DnaK ATPase activity. It is well known that the basal expression level of both GroEL and GrpE is enhanced by environmental stress 47–50. Therefore, the present results support the idea that the Se(IV) supplementation is a stressing event for L. reuteri Lb2 BM.…”
Section: Resultssupporting
confidence: 88%
“…More precisely, GrpE is a co‐chaperone working as a nucleotide exchange factor for DnaK (a heat shock protein belonging to the Hsp70 family) and it activates the DnaK ATPase activity. It is well known that the basal expression level of both GroEL and GrpE is enhanced by environmental stress 47–50. Therefore, the present results support the idea that the Se(IV) supplementation is a stressing event for L. reuteri Lb2 BM.…”
Section: Resultssupporting
confidence: 88%
“…Pressure treatment of microbial cells induces many changes in the bacterial cell, including inhibition of key enzymes, inhibition of protein synthesis, alterations in cell morphology and the cell membrane, as well as affecting the genetic mechanisms of the microorganism such as disruption of transcription and translation and cellular functions responsible for survival and reproduction (Patterson, 1999; Murchie et al , 2005; Torres & Velazquez, 2005; Vogel et al , 2005; Huppertz et al , 2006; Abe, 2007). Bacterial membrane damage has multiple effects, causing leakage of cellular material through the inner and outer membranes as well as nutrient uptake and disposal of cell waste, as seen in studies reporting increased sensitivity to sodium chloride (Chilton et al , 1997) and uptake of ethidium bromide and propidium iodide (Mackey et al , 1995; Ritz et al , 2001).…”
Section: Effect Of Hpp On Microbial Food Safetymentioning
confidence: 99%
“…Microarray and proteome analysis has yielded valuable insight into possible genes or proteins that seem to be involved in conferring HPP resistance or survival. Such work has mainly concentrated on food pathogens such as E. coli (Ishii et al , 2005; Malone et al , 2006), Listeria monocytogenes (Bowman et al , 2006) and lactic acid bacteria such as Lactobacillus sanfranciscensis (Vogel et al , 2005). These studies and others (Aertsen et al , 2004a, b, 2005) have revealed that HPP treatment induces, among others, oxidative stress, heat‐ and cold‐stress responses, an SOS response, up‐regulation of genes for chemotaxis, phosphotransferase systems, flagellar systems and genes involved in cell elongation and septum development.…”
Section: Effect Of Hpp On Microbial Food Safetymentioning
confidence: 99%
“…Lactic acid bacteria stress response to preservation processes Table1. Response mechanisms of LAB to various stress conditions encountered during food processing and the major stress proteins or enzymes involved in the response (adapted from Ananta & Knorr, 2004, Pavlovic et al, 2005Jofre et al, 2007;Franz & Holzapfel, 2011;Mota et al, 2013) .…”
Section: Gene Regulation In the Lab Stress Responsementioning
confidence: 99%